Between Tarhuntas and Zeus Polieus (Leuven)
xix, 255 s.
Keywords: "Anatolia is an area of the ancient world with a remarkable borderland character between the Greek and the Near Eastern worlds. The present book studies several ancient Anatolian cults and sanctuaries, focusing on the process of interaction between local cultures (Lycian, Carian, Pisidian, Cilician, Lydian, Pontic), Persians, Greeks and Romans. Which Greek practices did the natives adopt as part of their own tradition, especially in far-flung regions such as Pontus or Pisidia? How did these practices, together with the survival (or even revival) of ancient traditions, help forge a sort of regional identity in local sanctuaries? Which were the different roles played in this process by the local elites and the rural native populations? To answer such questions, each specific contribution presents a case study with a thorough analysis of the available epigraphic, numismatic, literary and archaeological evidence from a linguistic, historical and religious perspective. Gathered from a vast geographical area - from Ionia to Cilicia - this book explores different examples of these interactions expressed through local versions of major Greek and Anatolian deities: the Xanthian Leto, Ma of Comana, the Carian Sinuri, Mên Askaenos, Meis Axiottenos, Apollo Syrmaios, Artemis Sardiane, Meter Sipylene, a Cilician Zeus Ceraunius and the river gods." --